Estudo do potencial evocado auditivo de longa latência em um grupo de crianças deficientes auditivas usuárias de aparelhos de amplificação sonora individual: estudo de caso - Hoshii, Lia Auer (2010)
Introduction: Recent scientific studies use Long-Latency Auditory Evoked Potentials in order to measure the developmental status and plasticity limits of central auditory pathways. Goal: To study Long-Latency Auditory Evoked Potentials outcomes in hearing impaired children wearing hearing aids and personal sound amplification devices. Method: Case studies of five subjects, male and female, diagnosed with mild to profound neurosensory hearing loss, ages ranging from seven to 19 years old. The subjects were submitted to Long-Latency Auditory Evoked Potentials and Cognitive Potential (P300). The latency of components P1, N1, N2, P2 and P300 were analyzed. Prior evaluations consisting of inspecting the external acoustic meatus, tympanometry and pure tone audiometry were performed. Four of the subjects performed the Long-Latency Auditory Evoked Potentials only once. One subject performed the test twice, since he was discharged from speech therapy and stopped using the hearing aids for five months. Results: It was possible to measure the components P1, N1, P2, N2 and P300 for all subjects. Subject 1 presented delayed latency for components P1, N1 and P2 on the right ear, and no response for P1 and N1 on the left ear. Subject 2 presented no response for component P1 bilaterally. Subject 3 presented delayed latency for components P2 and N2 on the right ear and no response for P1 on the left ear. Subject 4 presented delayed latency for N2 and P300 on the right ear. Subject 5 presented delayed latency for components N1 and N2 bilaterally, for P2 on the left ear and no response for P1 on the right ear. The second test collected showed a delay in almost all components of the Long Latency Auditory Evoked Potentials, except for N1 and P2 on the right ear. Conclusions: It is possible to perform Long-Latency Auditory Evoked Potentials in hearing impaired children who wear hearing aids and personal sound amplification devices from the age of 8 years. Degree of hearing loss, lack of systematic use of personal sound amplification devices, and long term sound deprivation can affect the results of Long-latency Auditory Evoked Potentials., and consequently the neural plasticity process